2016
DOI: 10.1371/journal.pone.0165916
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Arthritic Activity of Schistosoma mansoni and Trichinella spiralis Derived-Antigens in Adjuvant Arthritis in Rats: Role of FOXP3+ Treg Cells

Abstract: A growing body of evidence supports the concept of helminths therapy in a variety of autoimmune diseases. Here, we aimed to investigate the protective effects of autoclaved Schistosoma mansoni antigen (ASMA) and Trichinella spiralis antigen (ATSA) on the clinical and immunopathological features of rheumatoid arthritis (RA). Adjuvant arthritis was induced by subcutaneous and intradermal injections of complete Freund’s adjuvant into the plantar surface of the right hind paw and the root of the tail, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Trichinella sp infection or their products protect experimental hosts from several immune diseases 25 such as type 1 diabetes (T1D) in NOD mice, 26 inflammatory bowel diseases (IBD), [27][28][29][30][31][32][33][34] experimental autoimmune encephalomyelitis (EAE) 35,36 and adjuvant arthritis. 37 Regarding other helminths, Th2 signals were reported to be essential for the anti-arthritic effects. [6][7][8] Recently, Cheng et al 38 reported…”
Section: Discussionmentioning
confidence: 99%
“…Trichinella sp infection or their products protect experimental hosts from several immune diseases 25 such as type 1 diabetes (T1D) in NOD mice, 26 inflammatory bowel diseases (IBD), [27][28][29][30][31][32][33][34] experimental autoimmune encephalomyelitis (EAE) 35,36 and adjuvant arthritis. 37 Regarding other helminths, Th2 signals were reported to be essential for the anti-arthritic effects. [6][7][8] Recently, Cheng et al 38 reported…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current studies suggest that early infection of certain parasites may prevent the development of autoimmune diseases, including allergic disease and RA [7], and the mechanisms are associated with immune responses mediated by parasite infection. For example, it has been shown that Schistosoma japonicum infection and Trichinella spiralis derived antigen could reduce the severity of collageninduced arthritis [8], via immune reactions related to IL-4 and Treg Cells mediated by parasite antigens in CIA mice.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding on the helminths therapy targeting arthritis, experimental infections with S. japonicum, S. mansoni, Ascaris suum and Hymenolepsis diminuta, or administrations of their proteins have been shown to possess inhibitory effects on murine collagen-induced arthritis [17][18][19][20][21]. In thses studies, antiarthritic activity is mediated by up-regulation of the Foxp3 + Tregs with subsequent favorable modulation of both pro-and anti-in ammatory cytokines [20]. We speculated that C. sinensis, a liver uke found predominantly in Asia including Korea and China, could be an alternative candidate of Schistosoma.…”
Section: Discussionmentioning
confidence: 99%
“…First, we could not clarify the exact mechanism in the inhibition of Th17 response. However, this might be mediated by upregulation of regulatory cell populations such as CD4 + CD25 + Foxp3 + T cells or IL-10 secreting macrophages [20,26,27]. The inverse correlation of IL-10 with Th17 cells has been addressed both in humans and an experimental murine model [17,33].…”
Section: Discussionmentioning
confidence: 99%